THE ROAD TOWARDS SUSTAINABLE DEVELOPMENT: A CRITICAL AND COMPREHENSIVE STUDY - Bindlish, Mohit; Garg, Rajesh; Kumar, Ramesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Climate change is one of the most pressing global environmental issues, affecting areas such as food production, water resources, health, and energy. Tackling climate change requires a solid scientific understanding and coordinated action both nationally and globally. This paper examines these challenges. Historically, the industrialized world has been primarily responsible for the increase in greenhouse gas emissions, although developing nations are expected to contribute a larger share of future emissions. The projected impacts of climate change, under different scenarios, are likely to affect food production, water availability, coastal communities, forest ecosystems, health, and energy security. Developing countries, with their lower adaptive capacity, are particularly vulnerable to these effects. The efforts of the UNFCCC and the Kyoto Protocol have proven insufficient in addressing the climate change challenge. A more effective approach involves adopting sustainable development practices, such as transitioning to environmentally friendly technologies, enhancing energy efficiency, promoting renewable energy, conserving forests, reforesting, and implementing water-saving measures. For developing countries, the priority is reducing the vulnerability of their natural and socio-economic systems to climate change. Nations like India will face the dual challenge of implementing both mitigation and adaptation strategies, while also managing the costs and the potential impact on economic growth.